2002
DOI: 10.1063/1.1426419
|View full text |Cite
|
Sign up to set email alerts
|

The distance fluctuation criterion for melting: Comparison of square-well and Morse potential models for clusters and homopolymers

Abstract: We explore the distance fluctuation criterion ͑''Lindemann criterion''͒ for melting transitions. Distances from average positions in accord with Lindemann, or interparticle distances, in accord with Jellinek and Berry or Etters and Kaelberer, are examined. The primary goal is to determine which of these offers the more useful criterion. The choice of origin can sometimes effect the significance of the index. We study three systems with two kinds of potentials. They are all composed of 64 particles: ͑a͒ and ͑b͒… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(174 citation statements)
references
References 45 publications
7
164
0
Order By: Relevance
“…41 and 0.1-0.15 in Ref. 40. This also validates the theory of fixed point for self-similar L-J potentials and the Eqs (6)- (18).…”
Section: Aip Advances 2 022108 (2012)supporting
confidence: 64%
See 1 more Smart Citation
“…41 and 0.1-0.15 in Ref. 40. This also validates the theory of fixed point for self-similar L-J potentials and the Eqs (6)- (18).…”
Section: Aip Advances 2 022108 (2012)supporting
confidence: 64%
“…Lindemann criterion has been applied to study solid-versusliquid behavior: distance-fluctuations cannot increase without destroying the lattice structure. 40 Here it has been found that the Lindemann ratio, contained in Eq. (18), is equivalent to the stability condition of recursion equation (6), which also indicates the inverse cascade at the GT is only determined by the intrinsic and instantaneous geometric structure, without any presupposition and relevant parameter.…”
Section: Aip Advances 2 022108 (2012)mentioning
confidence: 99%
“…SW model was introduced originally to understand simple liquid; 34 however, due to its analytic tractability it has become even more useful for colloidal system, [35][36][37] heterochain molecules, [38][39][40] and complex system, [41][42][43] among others.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…This phenomenology describes a smooth transition in ion accessibility from 0 to 1 is suggested in other studies, [44][45][46][47][48] the basis of which is fluctuating positions of the fixed and mobile ions, as well as the continuous profile of electron density around a given ion. The mean displacement of an ion from an equilibrium position was considered to be Ͼ0.1͑a i + b l ͒ Å.…”
Section: ͑43͒mentioning
confidence: 99%